STAT3, MYC, and EBNA1 cooperate through a ZC3H18 transcriptional network to regulate survival and proliferation of EBV-positive lymphomas. - Huanzhou Xu; Siva Koganti; Chenglong Li; Michael T McIntosh; Sumita Bhaduri-McIntosh (PLoS Pathogens)
Epstein-Barr virus (EBV), a common gamma-herpesvirus linked to various malignancies, exploits host cellular mechanisms to promote oncogenesis. Our previous research identified the zinc finger protein ZC3H18 as a novel component of the cellular DNA replication machinery in the context of EBV-driven tumorigenesis. We now demonstrate that ZC3H18 expression is upregulated in EBV-transformed and cancer cell lines, as well as in EBV-positive diffuse large B-cell lymphomas from AIDS patients, compared to their EBV-negative counterparts, supporting its activation by EBV. Our experiments show that ZC3H18 expression is regulated by the key oncogenic factors STAT3 and MYC, as well as the essential viral protein EBNA1. Using inhibitors and genetic knockdown, we find that suppressing STAT3, MYC, or EBNA1 leads to decreased ZC3H18 levels, reduced cell viability, and increased apoptosis in EBV-positive B lymphoma cells. Furthermore, ZC3H18, STAT3, MYC, and EBNA1 mutually support each other's expression through a complex transcriptional network. Notably also, ZC3H18 transcriptionally enhances components of the NF-κB pathway, contributing to NF-κB signaling even in the absence of the EBV oncoprotein LMP1, which is crucial for cell proliferation and survival of several EBV-associated malignancies. Our findings reveal a novel regulatory axis in EBV-positive cancer cells involving STAT3, MYC, EBNA1, & ZC3H18, also linking ZC3H18 to the NF-κB pathway independently of LMP1. The involvement of EBNA1 in this network may explain, at least in part, the preferential upregulation of ZC3H18 in EBV-associated tumors and highlights predictive and therapeutic possibilities for such cancers.